Coordination of movements: identification of age-related dynamics of its development in karate boys 7-11 years old - Svitlana Marchenko; Olha Ivashchenko; Oleg Khudolii; Vadym Verygin (Kharkiv State Academy of Physical Culture, 2024)
The purpose of the study is to identify the age-related dynamics of the manifestation of coordination among junior and pre-pubescent karate boys (7-11 years old) training in the karate section at the initial stage of preparation. Materials and methods. The study involved 65 children of younger and prepubertal age. They underwent testing of coordination abilities in order to determine the level of development and identify the features of their manifestation in accordance with age and skill level. The selected sample was divided into five ages 7, 8, 9, 10 11 years old, with 13 children in each group. The children and their parents were aware of all the features of the study and gave their consent to participate in the experiment. The technical level of the children corresponded to the students of the 10th, 9th, 8th grades of Kyu (orange, orange with a blue stripe and blue belt color). To solve the tasks, the following research methods were used: study and analysis of scientific and methodological literature, pedagogical observation, timing of educational tasks, testing of coordination abilities, pedagogical ascertaining experiment, methods of mathematical statistics. Results. One-way analysis of variance (ANOVA) showed a significant effect of the age factor on the level of indicators of coordination abilities for: differentiation of spatial-dynamic parameters of movements (F = 95.712; p = 0.000); reorganization of motor actions (F = 111.410; p = 0.000); differentiation of spatial-temporal parameters (F = 50.863; p = 0.000); coordination of hand movements (F = 96.764; p = 0.000); maintaining postural stability (F = 38.274; p = 0.000); maintaining vestibular stability (F = 61.291; p = 0.000). Conclusions. Based on the results of studies indicators of various manifestations of coordination, statistically significant age differences are observed between groups of boys aged 7 to 10 years (p < 0.05). At 10-11 years old, there are no significant statistically significant differences in all indicators (p > 0.05), except for dynamic balance (p < 0.05).